Transfer of training among non-traditional students in higher education: Testing the theory of planned behavior - Gegenfurtner, Andreas; Testers, Laurent (Frontiers in Education, 2022)
This study tested the predictive validity of Ajzen’s theory of planned behavior with a sample of 182 non-traditional students in higher education to develop our understanding of non-traditional students’ intentions to transfer trained knowledge and skills from university courses to the workplace. After completing their courses, a survey measured behavioral, normative, and control beliefs, transfer attitudes, perceived social norms, transfer self-efficacy, and transfer intentions. One year later, a follow-up survey measured transfer of training. Partial least squares-based structural equation modeling (PLS-SEM) revealed that behavioral beliefs were positively associated with transfer attitudes, normative beliefs were positively associated with social norms, and control beliefs were positively associated with self-efficacy. Transfer attitudes and transfer self-efficacy predicted transfer intentions. Social norms, however, were nonsignificantly associated with intentions. Transfer intentions and transfer self-efficacy predicted transfer one year after training. These findings are discussed in terms of their predictive validity of Ajzen’s theory and their educational implications for non-traditional students enrolled in higher education programs.